Comparação de dois índices de determinação do grau de trofia nas águas do Baixo Rio São José dos Dourados, São Paulo, Brasil - Maia, Amanda Alves Domingos [UNESP]; de Carvalho, Sérgio Luís [UNESP]; de Carvalho, Fernando Tadeu [UNESP] (FapUNIFESP (SciELO), 2015)
This Study conducted from February 2010 to January 2011, in the Baixo São José dos Dourados (BSJD), in the Unidade de Gerenciamento de Recursos Hídricos (UGRHI) 18, in order to determine the trophic level of the water calculating the trophic state index (TSI) The points of collection were at the direct and diffuse inputs and dammed stretch of the watercourse (points 1 and 2), intermediate (3) and confluence with the Paraná River (point 4). The samples were superficial, medium and approximately 1 m above the riverbed. At the laboratory was determined chlorophyll-a, total phosphorus and orthophosphate, water transparency was determined at the collect place. After those parameters was possible to classify the waters as oligotrophic and ultraoligotrophic.
Comparison of two indexes of determination of the trophic state in the waters of Baixo São José dos Dourados, São Paulo, Brazil
Keywords: Eutrophication; Trophic level; Trophic state index